The integration of GIS, AHP, and remote sensing methods for potential areas groundwater: case study for Pontian district, Johor, Malaysia - Syukri, Mohd Sahrul; Samat, Narimah; Ismail, Mohd Hasmadi (Zibeline International Publishing, 2021)
In Malaysia, production and conservation of groundwater are essential to the ecosystem’s climate and sustainability. The decline of groundwater level data is a related problem for managing water supplies in the Pontian District, Johor, particularly in rural areas. With demand for household water, agriculture and industrial use is still increasing. Studies-based Remote Sensing (RS) and Geographic Information System (GIS) have gained more advantages in groundwater exploration as it is rapid knowledge about the research and development tool. Therefore, the present study has conducted an example of mapping potential groundwater zones in the Pontian District, Johor, and assessing the factors leading to explore future groundwater opportunities. To identify possible groundwater areas, RS data and GIS are being used, and the data collected by the Department of Mineral and Geoscience Malaysia (JMG). The present study utilized integration between GIS through analytical hierarchy process techniques (AHP). Five different maps were prepared and studied for the potential groundwater area, such as Roughness, Topographic Wetness Index (TWI), Elevation, Curvature, and Slope. Weights in all the thematic maps assigned to each class using the AHP method on their characteristics and potential water capability. The production accuracy has checked using groundwater prospects information, and the process is approximately 87.5 percent accurate. The resulting map of groundwater capacity was graded into five groups-very good, good, moderate, low, and very low. The analysis shows that about 57.3 percent of the area occupies the low potential groundwater area. The potential zones of good and moderate groundwater are observed in 1.28 percent and 18.94 percent, respectively. Only in minimal areas is the area under perfect potential areas registered. The results from this study can be useful in the preparation and growth planning of related agencies in Malaysia, for possible groundwater exploration to provide a fast system and cost reduction and a shorter period.